PROFILE OF VISUAL FUNCTION AFTER PHACOEMULSIFICATION AT A SECONDARY HOSPITAL - Christina Aritonang; Sarah Nia Amru (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2026)
Background: Cataract is the leading cause of preventable blindness worldwide, with the highest burden in developing countries. In Indonesia, East Java has the highest incidence of cataract. Objective: To evaluate the visual function outcomes after phacoemulsification through a social service program at a secondary hospital in Gresik Regency, East Java, Indonesia. Methods This retrospective observational study included 40 patients undergoing phacoemulsification surgery (April 22 to May 15, 2025). Eligible patients were those with mature or immature cataracts, with preoperative vision ranging from mild impairment to blindness, according to WHO criteria. Postoperative evaluations were conducted on days 1 and 14. Data were obtained from medical records and analyzed with the Wilcoxon and Friedman tests using SPSS version 27. Results: Among 40 patients, 37.5% were severely visually impaired and 32.5% were blind preoperatively. Postoperatively, blindness declined to 11.5% on day 1 and 2.5% on day 14, with 45% achieving good vision. Visual acuity and contrast sensitivity showed significant improvement postoperatively (both p < 0.001). Surgical complications included iritis, Descemet’s membrane detachment, elevated intraocular pressure, and one patient did not receive an implant due to a posterior capsular rupture during the surgery. Conclusion: Visual function demonstrates significant early improvements phacoemulsification through this social service program, highlighting the value of assessing multiple visual function parameters in routine postoperative evaluation.